Analysis Of Building Area On Residential Comfort - Cecilia Irene (Universitas Syiah Kuala, 2023)
Homes are an essential aspect of human life. A house is where people live and carry out their daily activities. The home itself has several factors that can influence comfort. Starting from lighting, circulation, and climate, one of them is the room area. The size of the room itself can affect the comfort of the occupants because the size of the room will influence every activity carried out in the house. Apart from that, the size of the room will affect the space for movement, circulation, and so on, so the space required must be adjusted to the needs of the occupants. The research will use qualitative methods to analyze the area's comfort level and residents' comfort level in their activities. Based on the data obtained, this research shows that the area of the house can be a factor that influences inner comfort; this is because when the house is too narrow, the occupants will not feel comfortable because of limited space to move around and vice versa if the house has an area that is too large. This shows that the area of the house is one factor in the comfort of a home. Therefore, it is essential to pay attention to the area of the residence before starting construction.